Persepsi Siswa Tentang Kompetensi Sosial Guru PAK Dan Kompetensi Kepribadian Guru PAK Kontribusinya Terhadap Perilaku Siswa - Mayuni Lammaniur (Sekolah Tinggi Teologi Sriwijaya, 2022)
Abstract: This research was conducted using quantitative methods, namely by collecting data, analyzing data and testing hypotheses. There are 3 things that are the purpose of this research, namely: first to find out the contribution of the social competence of PAK teachers to student behavior, second to determine the magnitude of the contribution of the PAK teacher’s personality competence to student behavior, and third to find out the joint contribution between the social competence of PAK teachers and the personal competence of PAK teachers on the behavior of SMA Dharma Wanita PEMPROVSU High School students Class XI in 2017. From the results of this study showed a significant contribution between the social competence of PAK teachers (X1), to student behavior (Y) with the personal competence variable of PAK teachers (X2) being controlled, amounting to ry1. 2 = 0.539 with a t-test of 5.788, the price of ttable (5.788> 1.67) is obtained. There is a significant contribution between the personal competence of PAK teachers (X2) on student behavior (Y) with the social competence variable of PAK teachers (X1) being controlled, at ry2. 1 = 0.539 with a t-test of 5.788 and the price for ttable = 1.67 (5.788 > 1.67) is obtained. There is a significant contribution between the social competence of PAK teachers (X1) and the personal competence of PAK teachers (X2) together to students’ behavior (Y) of fh = 41.352 and the price for ftable = 4.02 (41.352> 4.02) , as big as (Y). R2y1.2 = 35.046%. The level of student behavior tendencies (Y) is in the fairly good category with 28 students (49.13%), the category is not good with 32 students (53.43%), for the tendency of social competence of PAK teachers (X1) the number of students 20 people (33.34%), the category is not good with the number of students 40 (66.66%) and the level of personality competency tendency of PAK teachers (X2) the category is not good with the number of students 39 people (65%) ). Abstrak: Penelitian ini dilakukan dengan metode kuantitatif yaitu dengan pengumpulan data, analisis data serta pengujian hipotesis. Ada tiga tujuan penelitian: pertama untuk mengetahui besarnya kontribusi kompetensi sosial guru PAK terhadap perilaku siswa, kedua untuk mengetahui besarnya kontribusi kompetensi kepribadian guru PAK terhadap perilaku siswa dan untuk mengetahui kontribusi secara bersama-sama antara kompetensi sosial guru PAK dan ketiga kompetensi kepribadian guru PAK terhadap perilaku siswa SMA Dharma Wanita PEMPROVSU Kelas XI Tahun 2017. Dari hasil penelitian ini menunjukan kontribusi yang signifikan antara kompetensi sosial guru PAK (X1), terhadap perilaku siswa (Y) dengan variabel kompetensi kepribadian guru PAK (X2) dikontrol, sebesar = 0,539 dengan uji-t 5,788 diperoleh harga (5,788>1,67). Terdapat kontribusi yang signifikan antara kompetensi kepribadian guru PAK (X2) terhadap perilaku siswa (Y) dengan variabel kompetensi sosial guru PAK (X1) dikontrol, sebesar = 0,539 dengan uji-t 5,788 dan diperoleh harga = 1,67 (5,788 > 1,67). Terdapat kontribusi yang berarti antara kompetensi sosial guru PAK (X1) dan kompetensi kepribadian guru PAK (X2) secara bersama-sama terhadap perilaku siswa (Y) sebesar = 41,352 dan diperoleh harga = 4,02 (41,352> 4,02 ), sebesar (Y). R2y1.2 = 35,046%. Tingkat kecenderungan perilaku siswa (Y) berada pada kategori cukup baik dengan jumlah siswa 28 orang (49,13%), kategori kurang baik dengan jumlah siswa 32 orang (53,43%), untuk kecenderungan kompetensi sosial guru PAK (X1) jumlah siswa 20 orang (33,34%), kategori kurang baik dengan jumlah siswa 40 (66,66%) dan tingkat kecenderungan kompetensi kepribadian guru PAK (X2) kategori kurang baik dengan jumlah siswa 39 orang (65%).